The impact of diet and physical activity on reducing inflammation in endometriosis - Niekurzak, Karolina; Flis, Blanka; Jędrak, Maciej; Józefiak, Maciej; Sobkiewicz, Piotr (Quality in Sport, 2025)
Introduction: Endometriosis is a chronic condition where tissue similar to the endometrium grows outside the uterine cavity, leading to pain, inflammation, and fertility issues. Its manifestations can affect various systems and organs. In recent years, there has been growing interest in the impact of diet and physical activity on alleviating pain associated with endometriosis. Purpose of the work: The aim of this paper is to review the latest knowledge regarding endometriosis and its systemic manifestations in the body. Endometriosis can contribute to changes in the microbiome, affect metabolism in the liver and adipose tissue, and may significantly impact women's mental health. Materials and methods: We conducted a literature review from 1993 to 2024 available in the PubMed database using the keywords: "endometriosis", "inflammatory disease", "microbiome", "diet", "physical activity " Results: The discussed studies indicate a clear correlation between endometriosis and the development of systemic inflammation, changes in the microbiome, and an increased risk of depression. Moreover, studies indicate that physical activity and the consumption of certain foods can influence the level of inflammation in the body, which in turn may reduce pain symptoms. A thorough examination of this issue will lead to a better understanding of the nature of endometriosis and enable the discovery of new treatment strategies.